Acute Spinal Epidural Hematoma as a Complication of Dry Needling: A Case Report. Issue 3 (22nd February 2019) - Berrigan, William A.; Whitehair, Curtis L.; Zorowitz, Richard D.
Abstract : Dry needling is a procedure commonly performed for the relief of myofascial pain disorders. The procedure is generally well tolerated. Adverse events often are mild, but severe complications have been reported. This case report describes an acute spinal epidural hematoma as a complication of dry needling. It is a reminder to the performing physician or therapist to take specific precautions when placing a needle near the spine. Sudden onset of neuropathic pain after needling therapy in and around the spine should prompt emergency assessment with possibly advanced spine imaging to evaluate the integrity of the spinal cord. Level of Evidence: V